Effect of nitrate concentration on growth of green microalga Haematococcus pluvialis under laboratory conditions - Thom, Le Thi; Tam, Luu Thi; Mai, Dinh Ngoc; Lan Anh, Hoang Thi; Hoai Thu, Ngo Thi; Ha, Nguyen Cam; Hong, Dang Diem (Academia Journal of Biology, 2013)
Astaxanthin is a pigment that belongs to the family of carotenoids and it is one of the major carotenoids supplied in aquaculture. In addition to its role in the coloration of aquatic animals, this pigment possesses several important bioactivities, including antioxidation, enhancement of immune response on anticancer activities. Although astaxanthin can be synthesized by plants, bacteria, a few fungi, and green algae, Haematococcus pluvialis is the current best source of natural astaxanthin. Although the feasibility of continuous production of astaxanthin by vegetative motile cells has been recently demonstrated, the most common production process consists in separating the biomass production phase culture and the astaxanthin accumulation phase one. In addition to light and temperature, nutrients (including N) play important role in the cell division and in the accumulation of astaxanthin of H. pluvialis. This work aimed to investigate effects of nitrate concentration on growth of microalga H. pluvialis. The highest cell density was 1.74 × 106 cells/mL after the 36th days of cultivation at RM medium contained nitrate concentration of 876 mg/L. At this concentration, the ratio of vegetative cells was higher than other nitrate concentrations. Chlorophyll a and astaxanthin contents yielded 2081 and 1053 µg/L, respectively. In addition, protein content tended to decrease during cultivation process at all tested nitrate concentrations.